The modelling and designing of E-Supervised (E-SUV) for Distance Learning Centre - Shuib, Salehuddin; Hamid, Suhardi; Hanizan, H. S; Din, Roshidi; Jusoff, Kamaruzaman (World Scientific and Engineering Academy and Society (WSEAS) Stevens Point, Wisconsin, USA, 2009)
E-services is a suite of web-based products brings profound changes in business models and value chains especially for Professional and Continuing Education Centre (PACE) environment due to its responsibility to manage all courses provided by every faculty to private colleges. PACE is currently running resourcefully but it is facing a few problems such as the difficulties of each faculty officer to get information about private colleges, and a lack of information management in private colleges itself. Therefore, the objective of this study is to propose a model of e-service application called E-Supervised (E-SUV) to provide the information related to twinning programmes between Universiti Utara Malaysia (UUM) and private colleges by enabling users to interact via portal by using the UML-based Web Engineering (UWE) approach. This methodology includes four modeling activities which are requirement analysis, conceptual model, navigation model and presentation model. This research results in a web-based environment consisting of major modules such as profiles, forums, and email service for users to utilize. In a nutshell, UWE approach is a viable option to facilitate e-services in education environment and thus could serve as a guideline model of future edistance learning centre. Rigorous tests to see how this model behaves under real-life practice would be a way forward to identifying its effectiveness.